Early modern literary afterlives - Chaghafi, EL (2012)
My thesis explores the posthumous literary life in the early modern period by examining responses to ‘dead poets’ shortly after their deaths. Analysing responses to a series of literary figures, I chart a pre-history of literary biography. Overall, I argue for the gradual emergence of a linkage between an individual’s literary output and the personal life that predates the eighteenth century. Chapter 1 frames the critical investigation by contrasting examples of Lives written for authors living before and after my chosen period of specialisation. Both these Lives reflect changed attitudes towards the writing of poets’ lives as a result of wider discourses that the following chapters examine in more detail. Chapter 2 focuses on the events following the death of Robert Greene, an author often described as the first ‘professional’ English writer. The chapter suggests that Greene’s notoriety is for the most part a posthumous construct resulting from printed responses to his death. Chapter 3 is concerned with the problem of reconciling a poet’s life-narrative with the vita activa model and examines potential causes for the ‘gap’ between Sir Philip Sidney’s public life and his works, which continues to pose a challenge for biographers. Chapter 4 examines the evolution of Izaak Walton’s Life of Donne. The ‘life history’ of Walton’s Lives, particularly the Life of Donne, reflects an accidental discovery of a biographical technique that anticipates literary biography. My method is mainly based on bibliographical research, comparing editions and making distinctions between them which have not been made before, while paying particular attention to paratextual materials, such as dedications, prefaces and title pages. By investigating assumptions about individual authors, and also authorship in general, I hope to shed some light on a promising new area of early modern scholarship and direct greater scrutiny towards the assumptions brought into literary biography.